(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
The health is described in Charak Samhita under different titles along with its process to attain the health i.e., Arogyata, Sukha & Sukhayu, immune person etc. Rasayana & Vajikarana are the branches among the eight branches of Ayurveda and its result is shown as Swasthasyorjaskarah which are directly related to health promotion. A specific concept is also mentioned in Charak Samhita about absolute health is known as Naishthiki Chikitsa. The term Swasthasyorjskar Chikitsa is the Urjaskar therapy for Swastha Person. A medically fit (Arogya) person who achieve well being (Sukhayu) by following its tools and educative measures, should seek for promoted status of excellence of health or health plus. For this Swasthasyorjskar chikitsa is prescribed. When a person achieve maintenance of excellent status of health then only he can aspire for the absolute health status i.e. Nihshesh dukhnivritti through Yoga and Naishthiki chikitsa. Hence in Charak Samhita there is prescribed the provision of Swathasyorjaskar Chikitsa for healthy one also.